Geometrical constraint change determines organized collective migration of follower cells - Mitsuru Sentoku; Masaharu Endo; Miki Takei; Wataru Hanamoto; Kenji Yasuda (Scientific Reports)
Abstract Spatial confinement plays a critical role in shaping collective cell migration, particularly in regulating interactions between leader and follower cells and among follower cells themselves. However, how changes in confinement geometry influence migration dynamics and cell-to-cell interactions remains poorly understood. This study leverages a novel microchannel design to systematically dissect the interplay between spatial confinement and collective cell behavior in endothelial-like cells (MILE SVEN 1). In a single-cell-wide T-shaped branching structure, rear cells selected alternate pathways, avoiding direct alignment with preceding cells. This highlights how spatial geometry mediates follower-follower interactions by encouraging dynamic rearrangements within the cell train. Ladder-like branching structures with consistent total pathway widths showed that dividing and reassembling cell trains had minimal impact on migration velocity, provided no compression or expansion occurred. Wide-narrow-wide patterns demonstrated distinct effects: stepwise transitions accelerated cells in narrow sections, increasing directional alignment driven by spatial restriction, followed by decreased alignment in wider regions. Gradual transitions maintained stable alignment and minimized disruptions, emphasizing the importance of smooth geometrical transitions in preserving robust collective behavior. These findings reveal how spatial confinement integrates follower-follower interactions and dynamic realignment. By linking geometric transitions to collective cell dynamics, our study advances the understanding of physical guidance mechanisms and offers a platform for investigating spatial influences on migrating cellular systems.